Bioequivalence Assessment of Metformin Tablet Formulations of Bangladesh (Journal of Scientific Research, 2014)
Six marketed oral antidiabetic metformin tablets in Bangladesh have been studied for their drug content, release profile and glucose lowering capacities. This sort of study is a good indicator for in vivo evaluation of the quality of an oral antidiabetic preparation. Marketed preparations of metformin-HCl from different manufacturers were randomly chosen for this study. The drug content was within the United State Pharmacopoeia (USP) specified limit (95-105%) in all cases. The blood glucose levels were investigated in streptozotocin-induced diabetic rats (SIDRs) after 5 hours of single dose (110 mg/kg body weight) treatment of the products; significantly (p